The dilemma of re-licensing DWI offenders: The offenders' point of view. (February 2016) - Nadeau, Louise; Vanlaar, Ward; Jarvis, Juliette; Brown, Thomas G.
Highlights: Prediction of risk in DWI relicensing assessment is uncertain. In focus groups, offenders considered false positive or false negative error risk. Offenders generally pronounced false negative error as more fair. More recidivists preferred false positive error, predicting recidivism more likely. Offender perspectives can be useful for societally coherent DWI prevention policy. Abstract: In many jurisdictions, drivers convicted for the first-time of driving while impaired by alcohol undertake a risk assessment that will determine the severity of sanctions and the remedial measures they must follow as requisites for re-licensing. There is uncertainty inherent in the assessment of risk for recidivism, however, many offenders feel unfairly assessed and discommoded by the decision-making process and its consequences. The objective of this qualitative study was to gain insight into the perspectives of offenders regarding re-licensing decision making and sanctioning. Specifically, in focus groups first-time offenders and recidivists were probed as to whether they favoured erring on the side of road safety in decision making, with its consequent greater risk of false positive assessments, or erring on the side of maintaining driving privileges, with its consequent greater risk of false negative assessments. In general, participants preferred a higher probability of false negative vs. false positive assessments. Most cited the consequences of sanctions and remedial measures as too severe to impose them on potentially low-risk drivers, as the assessment and monitoring protocols' limitations could lead to non-equitable treatment. At the same time, recidivists evoked a greater preference for a higher probability of false positive assessments compared to first-time offenders, as they believed that recidivism was more likely to follow a first conviction than did first-time offenders. This information can be useful for a more comprehensive and societally coherent exercise of DWI prevention policies.